مفهوم الكتابة في الخطاب القرآني : دراسة موضوعية - بدران، فداء بسام صدقي (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2019)
The purpose of this research is to study the concept of inscribing in the Quranic discourse. It also explains the approach of the Holy Quran in determining the purpose and origin of inscribing and its importance. Inscribing preserves the secrets of civilizations and glories of mankind and it is granted by Almighty Allah to man in honor of him. Despite Prophet Muhammad (Peace be upon him) being illiterate, this description is an honor for him rather than a deficiency or a defect since he was the most explicit (in speech) among the Arabs whose culture prescribed the exact word for the most precise and concise meaning. The inductive method was used in this research to examine the verses related to inscribing to reach general judgment. Furthermore, the analytical method was used to study the concept of inscribing from several references and sources. The study also discussed the evidence and devised possible judgments to reach the following important results: inscribing is a blessing and divine advantage which Almighty Allah has distinguished humans with in order to preserve his knowledge, thoughts, and glories of his achievement. Almighty Allah has also honored humans with inscribing to document contracts, debts and financial transactions in order to preserve the rights of people. If it were not for inscribing, the books of Hadith, Sirah and the knowledge of earlier civilizations would not have come to mankind